How Industry 4.0 technologies and open innovation can improve green innovation performance? - Mubarak, Muhammad Faraz; Tiwari, Suman; Petraite, Monika; Mubarik, Mobashar; Raja Mohd Rasi, Raja Zuraidah (Emerald Publishing Limited, 2021)
Purpose – This study investigates the impact of Industry 4.0 technologies on green innovation performance. In this relationship, the mediating role of green innovation behavior is also studied. Moreover, open innovation is tested as a mediator between Industry 4.0 technologies and green innovation behavior. Design/methodology/approach – A quantitative research method is adopted in which a structured questionnaire was used to collect data from 217 manufacturing firms of Malaysia. After collecting data, the partial least squares-structural equation modeling (PLS-SEM) technique is applied to analyze data and test the hypothesis of study. Findings – It is found that Industry 4.0 positively impacts open innovation which leads to green innovation behavior. Also, the former lays positive impact on green innovation behavior which leads to improve green innovation performance. Research limitations/implications – The authors conclude that Industry 4.0 technologies can play an important role to improve green innovation performance of Malaysian manufacturing firms by managing open innovation for green innovation behavior which further improves the green innovation performance. In this context, it is recommended that strategists and policymakers should undertake the role of open innovation and Industry 4.0 technologies to promote environment-friendly innovations and to promote the green behavior in companies. The authors suggest hereby that firms should be given incentives to adopt and utilize Industry 4.0 technologies and collaborative innovation interactions – as they foster a climate for sustainable green innovations (which is also a key component to achieve competitive advantage) and a growing concern nowadays. Practical implications – First of all the research contributes to achieving the broader of United Nations to promote sustainable innovation through green innovations. Moreover, the companies can also incorporate the findings and insights of this study while devising their policies to foster green innovations. Originality/value – This research has done the novel contribution by bridging the gap between open innovation approach and sustainability fields while promoting green innovations in small and medium enterprises (SMEs). These two research fields are rarely studied in previous studies by focusing open innovation particularly. Hence, the authors suggest researchers to undertake these fields to further enhance the level of scholarship between innovation management and sustainability. Also, the authors recommend considering technological orientation and technological absorptive capacity of firms to improve green innovations. The current study has investigated the SMEs perspective in general irrespective to their sectoral differences, thus, for future researchers the authors suggest investigating the sector-wise comparison, i.e. electrical and electronics sector, chemical sector, etc.; or service and manufacturing sector differences.